HIV Infection with Membranous Nephropathy in a Low HIV Prevalent Muslim Country, Bangladesh: A Case Report (Journal of Medicine, 2015)
The most common renal manifestation of Human immunodeficiency virus (HIV), is HIV associated nephropathy (HIVAN). In this report, we describe a case that was referred for evaluation of proteinuria. Diagnostic workup revealed HIV infection with membranous nephropathy (MN). As he had sub-nephrotic range proteinuria and normal renal function we did not start any treatment for membranous nephropathy and for anti-retroviral therapy he was sent to a referral center. Being an uncommon variety of nephropathy in HIV infected patient in one of the lowest HIV prevalent country, we are reporting the case.DOI: http://dx.doi.org/10.3329/jom.v16i1.22408 J MEDICINE 2015; 16 : 61-63